Implementasi Sistem Informasi Administrasi Prodi PTIK Universitas Bung Hatta - Khairi, Ashabul; Diasno, Renonaldy Pratama (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This study aims to develop a web-based administrative information system for the Program of Educational Technology and Computer Engineering at Universitas Bung Hatta, replacing the previously used manual methods. The developed system is designed to manage student thesis data, lecturer documents, and accreditation processes. The development method applied is the waterfall model, which includes stages of analysis, design, coding, testing, and maintenance. Results from validation testing indicate that the system is ready for use and suitable for further research. The information system features menus such as academic, administration, lecturers, alumni, and news, and utilizes a MySQL database. The use of responsive PHP programming facilitates data access and processing. The implementation of this system is expected to enhance the efficiency and effectiveness of administrative management and simplify the accreditation process for the PTIK program.